Creating early childhood Islamic spiritual education with cartoons Rara and Nussa as a method for Quranic learning - Kamilah, Nurul; Sutrisno, Sutrisno (Thufuli, 2025)
The aims of this study is to determine the content of the Qur'an in the film Nusa and Rara. The education of the Qur'an holds significant importance for children. Individuals can attain knowledge of God through the Qur'an. The Nussa and Rara animation represents an effective digital medium. Facilitating children's comprehension of the Qur'an and incorporating Islamic values into their everyday practices. Because Merdeka curriculum and Profil Pelajar Pancasila are used in schools, so that learning the Qur'an can be integrated into children's daily lives. This study employs descriptive qualitative methodologies. The data source is the animated film "Nussa and Rara." The data collection method involves analyzing three specific episodes from the animated film Nussa and Rara: "Who Are We," "Free Rewards," and "Brother Nussa." The method of data analysis employed is content analysis of the chosen episodes. Aligning with verses from the Qur'an and pertinent Islamic literature. This research identifies several values of Islamic religious education in the film, specifically faith, worship, and monotheism as This animation is appropriate for preschool children due to its brief duration and incorporating of a conclusion at the story's end. This research concludes that Nusa and Rara are appropriate for early childhood viewing, as they correspond with children's characteristics and incorporate moral and Islamic religious values, thereby aiding in children's learning of the Quran. Furthermore.  This film relates to the Merdeka curriculum and the Profil Pelajar Pancasila.  The integration of the Quran are happen in daily life.